2006
DOI: 10.1007/s00595-006-3244-3
|View full text |Cite
|
Sign up to set email alerts
|

Familial Epidermoid Cysts of the Spleen: Report of Two Cases

Abstract: The familial occurrence of epidermoid cysts of the spleen is rare, with only six cases having ever been reported, to our knowledge. We recently diagnosed epidermoid cysts of the spleen in a mother and son. First, a 15-year-old boy was admitted to our hospital for management of blunt abdominal trauma. Computed tomography (CT) showed a ruptured large splenic cyst with an intraabdominal hematoma. We performed a splenectomy, and histopathological examination confirmed the existence of an epidermoid cyst of the spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…We did not find a similar image in the literature, except in one case of a spontaneously ruptured congenital splenic cyst, which had a CT appearance resembling to our case [23]. Retrospectively, we believe that the nonenhancing areas of splenic parenchyma in the vicinity of the splenic cyst wall were not consistent with perfusion defects but represented pockets of perisplenic fluid.…”
Section: Discussioncontrasting
confidence: 48%
“…We did not find a similar image in the literature, except in one case of a spontaneously ruptured congenital splenic cyst, which had a CT appearance resembling to our case [23]. Retrospectively, we believe that the nonenhancing areas of splenic parenchyma in the vicinity of the splenic cyst wall were not consistent with perfusion defects but represented pockets of perisplenic fluid.…”
Section: Discussioncontrasting
confidence: 48%
“…However, as ruptured cysts are even more uncommon, we concluded that 20 studies have been published addressing 21 cases with ruptured non-parasitic splenic cysts, the oldest study being published in 1960 (table 2). 8–26 Age varies from 6 to 46 years old with our study presenting the oldest patient. All cases presented with abdominal pain which was sometimes accompanied by left shoulder pain, nausea or vomiting.…”
Section: Discussionmentioning
confidence: 89%
“…Kubo et al 4 reported that the splenic epidermoid cysts can generally be treated conservatively; however, symptomatic, ruptured, and infectious cysts require surgical intervention. 4 We also believe that an epidermoid cyst in the abdominal wall should be surgically treated. When findings of malignancy are doubtful, the tumor should immediately be removed surgically because there are reports of cancer developing from an epidermoid cyst.…”
Section: Discussionmentioning
confidence: 98%